Extended Renal Artery Denervation Is Associated with Artery Wall Lesions and Acute Systemic and Pulmonary Hemodynamic Changes: A Sham-Controlled Experimental Study. (29th October 2020) - Vakhrushev, Aleksandr D.; Condori Leandro, Heber Ivan; Goncharova, Natalia S.; Korobchenko, Lev E.; Mitrofanova, Lubov B.; Lebedev, Dmitry S.; Mikhaylov, Evgeny N.
Abstract : Objectives . We sought to assess acute changes in systemic and pulmonary hemodynamics and microscopic artery lesions following extended renal artery denervation (RDN). Background . RDN has been proposed to reduce sympathetic nervous system hyperactivation. Although the effects of RDN on systemic circulation and overall sympathetic activity have been studied, data on the impact of RDN on pulmonary hemodynamics is lacking. Methods . The study comprised 13 normotensive Landrace pigs. After randomization, 7 animals were allocated to the group of bilateral RDN and 6 animals to the group of a sham procedure (SHAM). Hemodynamic measures, cannulation, and balloon-based occlusion of the renal arteries were performed in both groups. In the RDN group, radiofrequency ablation was performed in all available arteries and their segments. An autopsy study of the renal arteries was carried out in both groups. Results . The analysis was performed on 12 pigs (6 in either group) since pulmonary thromboembolism occurred in one case. A statistically significant drop in the mean diastolic pulmonary artery pressure (PAP) was detected in the RDN group when compared with the SHAM group (change by 13.0 ± 4.4 and 10.0 ± 3.0 mmHg, correspondingly; P = 0.04 ). In 5 out of 6 pigs in the RDN group, a significant decrease in systemic systolic blood pressure was found, when compared with baseline (98.8 ± 17.8 vs. 90.2 ± 12.6 mmHg, P = 0.04 ), and a lower mean pulmonary vascular resistance (PVR) (291.0 ± 77.4 vs. 228.5 ± 63.8 dyn ∗ sec ∗ c m − 5, P = 0.03 ) after ablation was found. Artery dissections were found in both groups, with prevalence in animals after RDN. Conclusions . Extensive RDN leads to a rapid and significant decrease in PAP. In the majority of cases, RDN is associated with an acute lowering of systolic blood pressure and PVR. Extended RDN is associated with artery wall lesions and thrombus formation underdiagnosed by angiography.